Engagement in Household Chores in Youth With Chronic Conditions: Health care Transition Implications. (January 2021) - Richards, Jordan; Nazareth, Meaghan; van Tilburg, Miranda A. L.; Jain, Nina; Hart, Laura; Faldowski, Richard A.; Coltrane, Chad; Hooper, Stephen R.; Ferris, Maria; Rak, Eniko
This study examined associations between chores engagement, self-management, and transition readiness in youth with chronic conditions. Youths with various chronic conditions attending a therapeutic camp, and their parents participated. Responses of 165 campers and their parents were analyzed (mean camper age 12.3 ± 2.6 years, 47.9% males, 79.4% White). The most common diagnoses were diabetes, spina bifida, cerebral palsy, and sickle cell anemia. Youth who completed chores manifested higher overall health care transition readiness (β ^ = 5.17, p = .026) and better communication with providers (β ^ = 2.98, p = .006) than youth who completed no chores. Higher chores frequency was not more predictive of higher health care transition readiness scores above and beyond the effects of having chores at all. These results suggest that responsible health care behaviors are related to similar actions in other areas of life. Assignment of chores may promote self-management and health care transition readiness in youth with chronic conditions.